Corrigendum to "Spectral determination of µa, µs and g from single and multiple scattering signals with one optically thick sample" Journal of Quantitative Spectroscopy & Radiative Transfer 245 (2020) 106868. (September 2020) - Tian, Peng; Mutisya, Stephen M.; Jin, Jiahong; Zheng, Shuai; Lu, Jun Q.; Hu, Xin-Hua
Highlights: A new and robust method for determination of absorption coefficient µ a, scattering coefficient µs and anisotropy factor g has been developed without integrating spheres based on the radiative transfer (RT) theory. The RT parameters are determined from the measured signals of forward transmittance dominated by light of single scattering and non-hemispherical diffuse reflectance and transmittance dominated by light of multiple scattering. An inverse algorithm based on GPU executed Monte Carlo simulations has been developed to rapidly obtain the RT parameters from the measured signals. The new method has been validated against the Mie theory with different sphere suspension samples in a spectral region of 460 to 1000nm. Uniqueness of the inverse solutions has been proved at selected wavelengths.